Stone Tool Variability and the Ecological Context of the Earliest Archaeological Record - Rogers, Michael J. (2013)
Keywords: dept.ant; faculty_collection; sabbatical_report

The Origins of Tool Use and the Earliest Archaeological Record. - Rogers, Michael J. (2007)
Keywords: dept.ant; faculty_collection; sabbatical_report

The African Acheulean - Sahnouni, Mohamed; Semaw, Sileshi; Rogers, Michael (The Oxford Handbook of African Archaeology, 2013)
This article argues that the Acheulean is perhaps the longest lasting cultural–technological tradition in human history, dating from around 1.7 to 0.3 Mya and roughly corresponding to the time during which H. Erectus and H. Heidelbergensis lived in Africa. Unlike earlier Oldowan technology, Acheulean cores — handaxes, cleavers, and picks — were standardised, of predetermined shape and made on large cobbles and flakes. The extensive Acheulean archaeological record throughout Africa over 1.4 million years described is testimony to the success of this technology’s makers in different habitats, altitudes, and settings, but also to its apparent conservative cultural nature: a learned tradition passed on through thousands of generations of highly mobile hominin groups with small population sizes. Although there are differences between Early and Late Acheulean technology, the makers of these tools may have undergone more significant changes with respect to the use of other technologies, strategic land use, and social life.
Keywords: dept.ant

Long-term hominin preference for the gallery forest edge: Insights from the Gona paleosols, Afar, Ethiopia - Stinchcomb, Gary E.; Rogers, Michael J.; Semaw, Sileshi (Quaternary Science Reviews, 2025)
The Gona Paleoanthropological Research Project area in the Afar Region of Ethiopia arguably contains one of the most complete records of archaeological sites anywhere in the world, from the earliest Oldowan dated to 2.6 Ma, to the Later Stone Age (LSA) dated to ca. 12-7 Ka. This makes Gona an ideal place to examine long-term trends in hominin-environment interaction. We revisited archaeological and hominin fossil sites at Gona and characterized the fossil soils using paleopedology and found evidence of paleo-Fluvisols, -Cambisols and -Vertisols. Greater than 70% of those archaeological sites spanning Oldowan to the Later Stone Age are found in buried paleosols with A-C and A-Bk-C paleosol profiles resembling modern-day Fluvisols or Fluvic Cambisols. Fluvisol morphology shows presence of bedding, incipient soil structure development and overprinting after burial. Stratigraphy and lithofacies show that these paleo-Fluvisols were proximal to the ancestral Awash River (Type I depositional system) or a distal fan channel (Type II depositional system). These data suggest that soil burial rates were rapid due to proximal flooding, where this would be a primary factor inhibiting soil development. This style of sedimentation and weathering resembles a narrow (5–10 m width) strip of land in a modern-day channel shelf and bar setting, separating the river from the adjacent gallery forest. A review of the literature shows that the frequent association of artifacts with paleo-Fluvisols may be prevalent throughout eastern Africa and indicates a long history of hominin reliance on a riverine ecosystem edge, proximal stream water and gallery forest resources within broader river valleys. The few older archaeological sites (e.g., Oldowan and Acheulian) found in/on more well-developed paleosols at Gona are an exception to this rule. These latter sites may hint at different land-use patterns and thus differing trajectories of hominin-environmental interactions. Because most paleosol studies at Gona and elsewhere in eastern Africa use paleo-Vertisols or other more well-developed calcareous soils to reconstruct paleoenvironment, there is a potential spatial and temporal decoupling between those well-studied paleosols and the more weakly-developed ones where archaeology is found.
Keywords: Archaeology; Artificial intelligence; Astronomy; Computer science; Enhanced Data Rates for GSM Evolution; Geography; Geology; Gona; Mathematics; Paleoecology; Paleontology; Paleosol; Physics; Preference; River corridors; Statistics; Term (time); dept.ant; peer-reviewed

Paleoenvironments of Gona, Ethiopia, between 3-1 Mya: Evidence from faunal analysis - Leiss, Amanda C.; Rogers, Michael J.; Semaw, Sileshi (American Journal of Physical Anthropology, 2020)
Keywords: dept.ant; peer-reviewed; ⛔ No DOI found

Technological variation in the earliest Oldowan from Gona, Afar, Ethiopia - Stout, Dietrich; Semaw, Sileshi; Rogers, Michael J.; Cauche, Dominique (Journal of Human Evolution, 2010)
Inter-site technological variation in the archaeological record is one of the richest potential sources of information about Plio-Pleistocene hominid behavior and evolution. However, appropriate methods for describing and comparing Oldowan assemblages have yet to be agreed upon, and interpretation of the early record remains highly controversial. Particularly salient is disagreement over whether the Oldowan is a single technological phenomenon or is more accurately divided into multiple regional and/or chronological traditions, perhaps including a less developed Pre-Oldowan phase in the late Pliocene. Some of this disagreement reflects theoretical and methodological differences between research traditions and some is more directly evidential. Here we present a framework for describing and interpreting Oldowan variation and apply it to three Pliocene assemblages (EG-10, EG-12, and OGS-7) from Gona, all dated to c. 2.6 million years (Ma). Results indicate proficient knapping and a full range of Oldowan reduction strategies in these earliest known occurrences, consistent with the idea of an Oldowan “technological stasis” from 2.6–1.6Ma. Patterns of variation in raw material selection and predominant reduction strategy at each site clearly indicate the importance of cultural transmission in the Oldowan, but confounding ecological and economic variation continue to render interpretation in terms of multiple tool making traditions or species inappropriate. We propose that cultural transmission and ecological adaptation should be recognized as complementary, rather than mutually exclusive, mechanisms in future attempts to explain Oldowan technological variation.
Keywords: Animals; Archaeology; Chaîne opératoire; Chi-Square Distribution; Cultural Evolution; Early Stone Age; Environment; Ethiopia; Fossils; Gona; Hominidae; Humans; Lithic technology; Paleolithic; Paleontology; Pliocene-Pleistocene boundary; Pre-Oldowan; Stone Age; Tool Use Behavior; animal; archaeological evidence; archeology; chi square distribution; cultural anthropology; cultural geography; dept.ant; dept.bio; environment; evolution; fossil; geochronology; hominid; human; paleontology; peer-reviewed; spatial variation; technological development; technology adoption; tool use

From nothing to something: the appearance and context of the earliest archaeological record - Rogers, Michael J.; Semaw, Sileshi (Sourcebook of Paleolithic Transitions: Methods, Theories, and Interpretations, 2009)
Before 2.6 million years ago (Ma), no archaeological record has been securely documented, and therefore there is no evidence of hominin tool use. Then, at 2.6–2.58 Ma, there is widespread evidence for tool manufacture and use at several archaeological sites, with undisputed stone tools and fossil fauna at Gona, Ethiopia. Additionally, the evidence from the earliest archaeological sites at Gona shows that the earliest stone tool makers were skilled flintknappers and were able to select high quality stone raw materials. The possible reasons behind this seeming abrupt transition from the absence of stone tools to the presence thereof include sampling biases, paleogeographic influences, gaps in the geological record, paleoenvironmental change, and changes in the record of hominin evolution.Based on our observations at Gona, the earliest use of flaked stone tools is likely to be slightly older than 2.6 Ma. These stone tools represent a significant change in behavior that set the stage for subsequent hominin evolution. The paleogeographic and paleoenvironmental evidence points to the earliest use of stone tools in certain settings: usually (but not always) close to raw material sources, and ecotones between riparian woodlands and open grasslands. The earliest stone tool makers were proficient, selective, and flexible in their reduction strategies. The variability we see in Pliocene artifact assemblages has much to do with different raw material sources.
Keywords: Early Stone Age; Gona; Oldowan; Paleoenvironments; Pliocene; Stone tools; dept.ant

Reconstruction and analysis of the DAN5/P1 and BSN12/P1 Gona Early Pleistocene Homo fossils - Baab, Karen L.; Rogers, Michael; Bruner, Emiliano; Semaw, Sileshi (Journal of Human Evolution, 2022)
Two Early Pleistocene fossils from Gona, Ethiopia, were originally assigned to Homo erectus, and their differences in size and robusticity were attributed to either sexual dimorphism or anagenetic evolution. In the current study, we both revisit the taxonomic affinities of these fossils and assess whether morphological differences between them reflect temporal evolution or sexual variation. We generated virtual reconstructions of the mostly complete ∼1.55 Ma DAN5/P1 calvaria and the less complete 1.26 Ma BSN12/P1 fossil, allowing us to directly compare their anterior vault shapes using landmark-based shape analysis. The two fossils are similar in calvaria shape to H. erectus and also to other Early Pleistocene Homo species based on a geometric morphometric analysis of calvaria landmarks and semilandmarks. The DAN5/P1 fossil bears a particularly close affinity to the Georgian H. erectus fossils and to KNM-ER 1813 (H. habilis), probably reflecting allometric influences on vault shape. Combined with species-specific traits of the neurocranium (e.g., midline keeling, angular torus), we confirm that these fossils are likely early African H. erectus. We calculated regression-based estimates of endocranial volume for BSN12/P1 of 882–910 cm3 based on three virtual reconstructions. Although BSN12/P1 is markedly larger than DAN5/P1 (598 cm3), both fossils represent the smallest adult H. erectus known from their respective time periods in Africa. Some of the difference in endocranial volume between the two Gona fossils reflects broader species-level brain expansion from 1.77 to 0.01 Ma, confirmed here using a large sample (n = 38) of H. erectus. However, shape differences between these fossils did not reflect species-level changes to calvaria shape. Moreover, the analysis failed to recover a clear pattern of sexually patterned size or shape differences within H. erectus based on our current assessments of sex for individual fossils.
Keywords: Africa; Animals; Biological Evolution; Brain; Brain evolution; Calvaria shape; Ethiopia; Fossils; Hominidae; Homo erectus; Intraspecific variation; Pleistocene; Sexual dimorphism; Skull; anatomy and histology; animal; brain; dept.ant; evolution; fossil; hominid; human evolution; intraspecific variation; morphology; peer-reviewed; reconstruction; sexual dimorphism; skull; temporal evolution

Archaeology and the origins of human cumulative culture: a case study from the earliest Oldowan at Gona, Ethiopia - Stout, Dietrich; Rogers, Michael J.; Jaeggi, Adrian V.; Semaw, Sileshi (Current Anthropology, 2019)
The capacity of Homo sapiens for the intergenerational accumulation of complex technologies, practices, and beliefs is central to contemporary accounts of human distinctiveness. However, the actual antiquity and evolutionary origins of cumulative culture are not known. Here we propose and exemplify a research program for studying the origins of cumulative culture using archaeological evidence. Our stepwise approach disentangles assessment of the observed fidelity of behavior reproduction from inferences regarding required learning mechanisms (e.g., teaching, imitation) and the explanation of larger-scale patterns of change. It is empirically grounded in technological analysis of artifact assemblages using well-validated experimental models. We demonstrate with a case study using a toolmaking replication experiment to assess evidence of behavior copying across three 2.6 Ma Oldowan sites from Gona, Ethiopia. Results fail to reveal any effects of raw material size, shape, quality, or reduction intensity that could explain the observed details of intersite technological variation in terms of individual learning across different local conditions. This supports the view that relatively detailed copying of toolmaking methods was already a feature of Oldowan technological reproduction at ca. 2.6 Ma. We conclude with a discussion of prospects and implications for further research on the evolution of human cumulative culture.
Keywords: dept.ant; peer-reviewed

Imposed Form in the Early Acheulean? Evidence from Gona, Afar, Ethiopia - Stout, Dietrich; Liu, Cheng; Muller, Antoine; Rogers, Michael; Semaw, Sileshi (Journal of Archaeological Method and Theory, 2025)
Keywords: Acheulean; Ancient history; Anthropology; Archaeology; Early Stone Age; Ethnology; Geography; Handaxe; History; Large cutting tool; Lithic technology; Pick; Pleistocene; Shaping; Sociology; dept.ant

New reconstruction of DAN5 cranium (Gona, Ethiopia) supports complex emergence of Homo erectus - Baab, Karen; Kaifu, Yousuke; Freidline, Sarah; Rogers, Michael; Semaw, Sileshi (Nature Communications, 2025)
The African Early Pleistocene is a time of evolutionary change and techno-behavioral innovation in human prehistory that sees the advent of our own genus, Homo, from earlier australopithecine ancestors by 2.8-2.3 million years ago. This was followed by the origin and dispersal of Homo erectus sensu lato across Africa and Eurasia between ~ 2.0 and 1.1 Ma and the emergence of both large-brained (e.g., Bodo, Kabwe) and small-brained (e.g., H. naledi) lineages in the Middle Pleistocene of Africa. Here we present a newly reconstructed face of the DAN5/P1 cranium from Gona, Ethiopia (1.6-1.5 Ma) that, in conjunction with the cranial vault, is a mostly complete Early Pleistocene Homo cranium from the Horn of Africa. Morphometric analyses demonstrate a combination of H. erectus-like cranial traits and basal Homo-like facial and dental features combined with a small brain size in DAN5/P1. The presence of such a morphological mosaic contemporaneous with or postdating the emergence of the indisputable H. erectus craniodental complex around 1.6 Ma implies an intricate evolutionary transition from early Homo to H. erectus. This finding also supports a long persistence of small-brained, plesiomorphic Homo group(s) alongside other Homo groups that experienced continued encephalization through the Early to Middle Pleistocene of Africa. The origin and dispersal of Homo erectus, a long-lived and geographically widespread human ancestor, are unclear despite a rich fossil record. Here, the authors reconstruct the face from a Homo erectus cranium from Gona, Ethiopia, dated to 1.5-1.6 million years ago, providing insights into the evolutionary transition from early Homo to H. erectus.
Keywords: Crania; Early Pleistocene; Hominidae; Homo erectus; Human evolution; Pleistocene; Sensu; Skull; dept.ant

The Oldowan-Acheulian Transition: Is there a “Developed Oldowan” Artifact Tradition? - Semaw, Sileshi; Rogers, Michael; Stout, Dietrich (Sourcebook of Paleolithic Transitions: Methods, Theories, and Interpretations, 2009)
The phrase “Developed Oldowan” (DO) was originally coined by M. Leakey to describe a technologically “advanced Oldowan” artifact tradition, that preceded the Acheulian Industry. M. Leakey further identified three stages of the DO which she labeled as the DOA, DOB and DOC. The DO (sensu lato) has been generally recognized as transitional to the Acheulian, but the status of the DOB and the DOC remains unclear. In addition to a lack of clarity in terms of classification, the DO also suffers from a lack of secure radiometric dates, even at Olduvai where it was first identified. Despite such shortcomings, archaeologists still assign assemblages into the DO, as supposedly “intermediate” or transitional between the Oldowan and the Acheulian. However, a closer look at the DO assemblages from Olduvai Gorge and other sites in Africa and the Middle East shows that the artifacts assigned into this tradition are not technologically drastically different from the preceding Oldowan. Probably the flaking characteristics of the raw material types (e.g., quartzite and limestone, and to a lesser extent basalt) and the original shape of the cobbles used by hominins may have played a major role in the final shape of the “distinctive” artifact types (such as spheroids/subspheroids) used for assigning assemblages into the DO. Further, both the DOB and the Acheulian appeared ˜1.7 million years ago (Ma) in the archaeological record, making it unlikely that the DO is a transitional artifact tradition that preceded the Acheulian. Our preliminary evaluation of the archaeological record at Gona, Ethiopia and elsewhere suggests a fairly abrupt appearance of the Acheulian after a temporally rapid transition from the Oldowan.
Keywords: Developed Oldowan; Early Acheulian; Oldowan; Oldowan-Acheulian transition; dept.ant

Cutmarked bones from Pliocene archaeological sites at Gona, Afar, Ethiopia: implications for the function of the world's oldest stone tools - Dominguez-Rodrigo, Manuel; Pickering, Travis Rayne; Semaw, Sileshi; Rogers, Michael J (Journal of Human Evolution, 2005)
Newly recorded archaeological sites at Gona (Afar, Ethiopia) preserve both stone tools and faunal remains. These sites have also yielded the largest sample of cutmarked bones known from the time interval 2.58-2.1 million years ago (Ma). Most of the cutmarks on the Gona fauna possess obvious macroscopic (e.g., deep V-shaped cross-sections) and microscopic (e.g., internal microstriations, Herzian cones, shoulder effects) features that allow us to identify them confidently as instances of stone tool-imparted damage caused by hominid butchery. In addition, preliminary observations of the anatomical placement of cutmarks on several of the recovered bone specimens suggest that Gona hominids may have eviscerated carcasses and defleshed the fully muscled upper and intermediate limb bones of ungulates-activities that further suggest that Late Pliocene hominids may have gained early access to large mammal carcasses. These observations support the hypothesis that the earliest stone artifacts functioned primarily as butchery tools and also imply that hunting and/or aggressive scavenging of large ungulate carcasses may have been part of the behavioral repertoire of hominids by c. 2.5 Ma, although a larger sample of cutmarked bone specimens is necessary to support the latter inference. (c) 2004 Elsevier Ltd. All rights reserved.
Keywords: Africa; Carcass; Cutmarks; Defleshing/filleting; East Africa; Eastern Hemisphere; Ethiopia; Evisceration; Gona; Hominidae; Hominids; Mammalia; Pliocene; Stone tools; Sub-Saharan Africa; Ungulata; World; archaeological evidence; dept.ant; hominid; peer-reviewed; tool use

The lower limb of Ardipithecus ramidus - Simpson, Scott W.; Levin, Naomi E.; Quade, Jay; Rogers, Michael; Semaw, Sileshi (American Journal of Physical Anthropology, 2019)
Keywords: dept.ant; peer-reviewed; ⛔ No DOI found

Landscape-scale variation in hominin tool use: Evidence from the Developed Oldowan - Braun, David R.; Rogers, Michael J.; Harris, John W. K.; Walker, Steven J. (Journal of Human Evolution, 2008)
The relationship between artifact manufacture, use, and discard in the Developed Oldowan is complex. Here we use digital-image-analysis techniques to investigate the intensity of reduction in single-platform cores of the Developed Oldowan of the Okote Member, Koobi Fora Formation. Data suggest that this method provides a more accurate measure of reduction intensity than previous applications of a unifacial-scraper model. Assemblages of single-platform cores excavated from extensive lateral exposures of the Okote Member provide insights into the relationship between raw-material availability and discard patterns. Variation in reduction intensity suggests that tools are not always discarded in patterns that would be predicted by the availability of raw material. Further, it appears that hominin transport decisions involved an assessment of the potential use-life of certain forms. Many aspects of Developed Oldowan technology conform to previously developed models of curated technologies. (C) 2008 Elsevier Ltd. All rights reserved
Keywords: Curation; Hominin behavior; Landscape archaeology; Oldowan; Pleistocene; Stone Age; Stone tools; dept.ant; hominid; image analysis; peer-reviewed; tool use

New evidence for hominin carcass processing strategies at 1.5 Ma, Koobi Fora, Kenya - Pobiner, Briana L.; Rogers, Michael J.; Monahan, Christopher M.; Harris, John W. K. (Journal of Human Evolution, 2008)
Reconstruction of early Pleistocene hominin carcass acquisition and processing behaviors are necessarily based at least in part on butchered fossil bones. This paper provides zooarchaeological and taphonomic analyses and behavioral interpretations of three similar to 1.5 million-year-old archaeofaunas from areas 1A and 103 in the Okote Member of the Koobi Fora Formation, northern Kenya: FwJj14A, FwJj14B, and GaJi14. These sites are all located in similar paleoenvironmental contexts, near shallow water with swampy, seasonally flooded areas, and some evidence for more wooded or gallery forest settings. Both individual specimen- and assemblage-level analyses of butchery-marked bones indicate that the hominins appear to have practiced similar butchery strategies at all of these sites, with butchery (defleshing, disarticulation, and marrow extraction) of both high- and low-ranked skeletal elements with no apparent preference for prey size, skeletal region, limb class, or limb portion. Only four tooth-marked specimens, including one likely crocodile-tooth-marked bone, are preserved in all three archaeofaunas. A paucity of limb epiphyses suggests that bone-crunching hyenids may have deleted these portions subsequent to hominin butchery. Strangely, there are no stone tools preserved with the 292 cut-marked and 27 percussion-marked faunal specimens (out of a total of 6,039 specimens), suggesting that raw material availability may have conditioned hominin lithic discard patterns at these locales. These assemblages increase our knowledge of the dietary behavior and ecology of Homo erectus, and provide support for variability in early Pleistocene hominin carcass foraging patterns. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Africa; Alligator; Bone modification; Butchery; Carnivory; Cut mark; Early Stone Age; East Africa; Homo erectus; Kenya; Koobi Fora; Oldowan; Percussion mark; Pleistocene; Rift Valley; Sub-Saharan Africa; Turkana; bone; carnivory; dept.ant; hominid; paleoecology; peer-reviewed; taphonomy

Raw material selectivity of the earliest stone toolmakers at Gona, Afar, Ethiopia - Stout, Dietrich; Quade, Jay; Semaw, Sileshi; Rogers, Michael J.; Levin, Naomi E. (Journal of Human Evolution, 2005)
Published evidence of Oldowan stone exploitation generally supports the conclusion that patterns of raw material use mere determined by local availability. This is contradicted by the results of systematic studies of raw material availability and use among the earliest known archaeological sites from Gona, Afar, Ethiopia. Artifact assemblages from six Pliocene archaeological sites were compared with six random cobble samples taken from associated conglomerates that record pene-contemporaneous raw material availability. Artifacts and cobbles were evaluated according to four variables intended to capture major elements of material quality: rock type, phenocryst percentage, average phenocryst size, and groundmass texture. Analyses of these variables provide evidence of hominid selectivity for raw material quality. These results demonstrate that raw material selectivity was a potential component of Oldowan technological organization from its earliest appearance and document a level of technological sophistication that is not always attributed to Pliocene hominids. (c) 2004 Elsevier Ltd. All rights reserved.
Keywords: Africa; Cognition; East Africa; Eastern Hemisphere; Ethiopia; Gona; Hominidae; Lithic technology; Oldowan; Pene; Pliocene; Raw materials; Sub-Saharan Africa; World; dept.ant; human activity; lithic fragment; peer-reviewed

The endocast from Dana Aoule North (DAN5/P1): A 1.5 million year-old human braincase from Gona, Afar, Ethiopia - Bruner, Emiliano; Holloway, Ralph; Baab, Karen L.; Rogers, Michael J.; Semaw, Sileshi (American Journal of Biological Anthropology, 2023)
The nearly complete cranium DAN5/P1 was found at Gona (Afar, Ethiopia), dated to 1.5–1.6 Ma, and assigned to the species Homo erectus. Its size is, nonetheless, particularly small for the known range of variation of this taxon, and the cranial capacity has been estimated as 598 cc. In this study, we analyzed a reconstruction of its endocranial cast, to investigate its paleoneurological features. The main anatomical traits of the endocast were described, and its morphology was compared with other fossil and modern human samples. The endocast shows most of the traits associated with less encephalized human taxa, like narrow frontal lobes and a simple meningeal vascular network with posterior parietal branches. The parietal region is relatively tall and rounded, although not especially large. Based on our set of measures, the general endocranial proportions are within the range of fossils included in the species Homo habilis or in the genus Australopithecus. Similarities with the genus Homo include a more posterior position of the frontal lobe relative to the cranial bones, and the general endocranial length and width when size is taken into account. This new specimen extends the known brain size variability of Homo ergaster/erectus, while suggesting that differences in gross brain proportions among early human species, or even between early humans and australopiths, were absent or subtle.
Keywords: Homo erectus; Homo ergaster; Lower Pleistocene; brain evolution; dept.ant; human evolution; paleoneurology; peer-reviewed

Postcranial fossils of Ardipithecus ramidus from Gona, Ethiopia - Simpson, Scott W.; Levin, Naomi E.; Quade, Jay; Rogers, Michael J.; Semaw, Sileshi (American Journal of Physical Anthropology, 2018)
Keywords: dept.ant; peer-reviewed; ⛔ No DOI found

Ardipithecus ramidus postcrania from the Gona Project area, Afar Regional State, Ethiopia. - Simpson, Scott W; Levin, Naomi E; Quade, Jay; Rogers, Michael J; Semaw, Sileshi (Journal of human evolution, 2019)
Functional analyses of the 4.4 Ma hominin Ardipithecus ramidus postcrania revealed a previously unknown and unpredicted locomotor pattern combining arboreal clambering and a form of terrestrial bipedality. To date, all of the fossil evidence of Ar. ramidus locomotion has been collected from the Aramis area of the Middle Awash Research Project in Ethiopia. Here, we present the results of an analysis of additional early Pliocene Ar. ramidus fossils from the Gona Project study area, Ethiopia, that includes a fragmentary but informative partial skeleton (GWM67/P2) and additional isolated manual remains. While we reinforce the original functional interpretations of Ar. ramidus of having a mixed locomotor adaptation of terrestrial bipedality and arboreal clambering, we broaden our understanding of the nature of its locomotor pattern by documenting better the function of the hip, ankle, and foot. The newly recovered fossils document a greater adaptation to bipedality in the Ar. ramidus ankle and hallux than previously recognized. In addition, a newly discovered scaphoid bone with a fusing os centrale provides further evidence about the nature of hominin hand evolution. Copyright © 2018 Elsevier Ltd. All rights reserved.
Keywords: *Fossils/ah [Anatomy & Histology]; *Hominidae/ah [Anatomy & Histology]; *Hominidae/ph [Physiology]; *Locomotion; Adaptation, Biological; Afar; Animals; Ardipithecus ramidus; Biological Evolution; Bipedality; Ethiopia; Fossils; Gona; Hominidae; Hominin; Locomotion; Pliocene; Postcrania; Skeleton; Skeleton/ah [Anatomy & Histology]; adaptation; anatomy and histology; animal; bipedalism; bone; cranium; dept.ant; evolution; fossil; hominid; locomotion; paleontology; peer-reviewed; physiology; skeleton

Isotopic evidence for plio-pleistocene environmental change at gona, ethiopia - Levin, Naomi E; Quade, Jay; Simpson, Scott W; Semaw, Sileshi; Rogers, Michael J (Earth and Planetary Science Letters, 2004)
A 4.5 Ma record of fluvial and lacustrine deposits is well exposed at Gona, in the Afar Depression of Ethiopia. We use isotopic values of pedogenic carbonate and fossil teeth to reconstruct Plio-Pleistocene environmental change at Gona. An increase in δ13C values of pedogenic carbonates since 4.5 Ma points to a shift from woodlands to grassy woodlands in the early Pliocene, -10.4 to -3.9‰ (VPDB), to more open but still mixed environments in the late Pleistocene, -3.0 to -1.4‰ (VPDB). This pattern is also seen in isotopic records elsewhere in East Africa. However, at 1.5 Ma the higher proportion of C4 grasses at Gona is largely a result of a local facies shift to more water-limited environments. The wide range of δ13C values of pedogenic carbonate within single stratigraphic levels indicates a mosaic of vegetation for all time intervals at Gona that depends on depositional environment. Elements of this mosaic are reflected in δ13C values of both modern plants and soil organic matter and Plio-Pleistocene soil carbonate, indicating higher amounts of C4 grasses with greater distance from a river channel in both the modern and ancient Awash River systems. δ18O values of pedogenic carbonates increase up-section from -11.9‰ in the early Pliocene to -6.4‰ (VPDB) in the late Pleistocene. The wide range of δ18O values in paleovertisol carbonates from all stratigraphic levels probably reflects short-term climate changes and periods of strong evaporation throughout the record. Based on the comparison between δ18O values of Plio-Pleistocene pedogenic carbonates and modern waters, we estimate that there has been a 6.5‰ increase in mean annual δ18O values of meteoric water since 4.5 Ma. δ18O values of pedogenic carbonate from other East African records indicate a similar shift. Increasing aridity and fluctuations in the timing and source of rainfall are likely responsible for the changes in δ18O values of East African pedogenic carbonates through the Plio-Pleistocene. © 2004 Elsevier B.V. All rights reserved.
Keywords: Africa; East Africa; Ethiopia; Gona; Isotopes; Paleoclimate; Paleosols; Pleistocene; Plio-Pleistocene; Pliocene; Sub-Saharan Africa; carbonate sediment; dept.ant; isotopic analysis; paleoenvironment; peer-reviewed; sediment chemistry

Paleoenvironmental changes during the last 6 million years at Gona, Afar Region, Ethiopia - Levin, Naomi E; Simpson, S.; Rogers, Michael J.; Semaw, S. (African Paleoecology and Human Evolution, 2020)
Keywords: dept.ant

Gona, Ethiopia: microcosm of the stone age - Rogers, Michael J.; Semaw, Sileshi; Stinchcomb, Gary E.; Quade, Jay; Levin, Naomi E.; Cauche, Dominique (Handbook of Pleistocene Archaeology of Afric, 2023)
The Gona paleoanthropological field project in the Afar region of Ethiopia has long been associated with the earliest Oldowan stone tools. However, over the last 20 years, ongoing research at Gona has expanded its contributions considerably, producing fossils of Ardipithecus kadabba, Ardipithecus ramidus, and Homo erectus, as well as additional archaeological evidence of the earliest Oldowan and early Acheulean. Moreover, in the last few years, the Gona team has turned its attention to the younger deposits exposed in its study area and discovered a surprising number of Middle Stone Age (MSA) and Later Stone Age (LSA) archaeological sites, mostly from the Late Pleistocene to the early-middle Holocene. While any sedimentary sequence is incomplete by virtue of episodic depositional and erosional events over time, we are struck by the relative completeness of the archaeological sequence at Gona (Quade et al., 2008). The hominin fossils attract deserved attention, but the Gona project may ultimately be best known for preserving arguably the most extensive, detailed, and continuous Stone Age or Paleolithic archaeological sequence in the world, all contained within a small 25 km × 10 km area, approximately half of the total project area.
Keywords: dept.ant

The Early Acheulean ~1.6–1.2 Ma from Gona, Ethiopia: Issues related to the emergence of the Acheulean in Africa - Semaw, Sileshi; Rogers, Michael J.; Cáceres, Isabel; Stout, Dietrich; Leiss, Amanda C. (The Emergence of the Acheulean in East Africa and Beyond: Contributions in Honor of Jean Chavaillon, 2018)
Konso in Ethiopia and Kokiselei in Kenya, both dated to ~1.7 million years ago (Ma), and FLK West, a recently reported site from Olduvai dated to 1.7 Ma, are the earliest Acheulean sites known in East Africa. Ongoing archaeological investigations at Gona, in the Afar Depression of Ethiopia, have also produced early Acheulean stone assemblages at several sites, estimated to ~1.6–1.2 Ma. A number of sites, including BSN-12 and OGS-12, have yielded archaeological materials comparable to the earliest Konso artifacts. The stone assemblages from the Gona sites consist of crudely made handaxes, cleavers, and picks, as well as Mode I (Oldowan) cores, and débitage. A variety of raw materials were exploited at Gona, with trachyte, rhyolite, and basalt being the most common.Our understanding of the behavioral and ecological background for the emergence of the Acheulean is still limited. Preliminary comparisons of BSN-12 and OGS-12 with other early Acheulean sites demonstrate variability in paleoecological settings as well as raw material use. Current archaeological evidence indicates that early Homo erectus/ergaster use of this new technology was already in place in East Africa ~1.75 Ma. At Gona and elsewhere in Africa, continued survey and excavations are needed to document sites with potential for yielding archaeological traces that will help our understanding of the Oldowan–Acheulean transition, the identity of the toolmakers, and the function of the early Acheulean Large Cutting Tools (LCTs).
Keywords: Ethiopia; Gona; Oldowan–Acheulean transition; Technical behaviors; dept.ant

Fossil Cercopithecidae from the Early Pliocene Sagantole Formation at Gona, Ethiopia - Frost, Stephen R.; Simpson, Scott W.; Levin, Naomi E.; Quade, Jay; Rogers, Michael J.; Semaw, Sileshi (Journal of Human Evolution, 2020)
The Early Pliocene Sagantole Fm. in the Gona Project area, Afar State, Ethiopia, is noted for discoveries of the early hominin Ardipithecus ramidus. A large series of fossil cercopithecid primates dated to between 4.8 and 4.3 Ma has also been collected from these sediments. In this paper, we use qualitative analysis and standard dental and postcranial measures to systematically describe the craniodental remains and tentatively allocate postcrania to taxa where we are able to. We then use these data to compare these specimens to fossil assemblages from contemporary sites, interpret their paleobiology, and discuss implications for the paleoecology of the Gona Sagantole Fm. We recognize three cercopithecid species in the Gona Sagantole Fm. Pliopapio alemui makes up approximately two-thirds of the identifiable specimens; nearly all of the rest are allocated to Kuseracolobus aramisi, and a single molar indicates the presence of a second, somewhat larger but morphologically distinct papionin. Among the Early Pliocene cercopithecids from Gona are also a number of postcranial elements. None of the postcranial remains are directly associated with any of the cranial material. Nonetheless, some of the distal humeri and proximal femora can be tentatively allocated to either Pl. alemui or K. aramisi based on a combination of size, as the latter is approximately 50% larger than the former, and morphology. If these assignments are correct, they suggest K. aramisi was primarily arboreal and similar to most extant colobines, whereas Pl. alemui was more mixed in its substrate use, being more terrestrially adapted than K. aramisi, but less so than extant Papio or Theropithecus. Thus, we interpret the predominance of Pl. alemui over K. aramisi is consistent with a somewhat more open environment at Gona than at Aramis. © 2020 Elsevier Ltd
Keywords: Animals; Ardipithecus ramidus; Cercopithecidae; Ethiopia; Female; Fossils; Gona; Kuseracolobus; Life History Traits; Male; Paleobiology; Papio; Pliocene; Pliopapio; Primates; Theropithecus; anatomy and histology; animal; cranium; dentition; dept.ant; female; fossil; fossil assemblage; hominid; life history trait; male; paleobiology; paleoecology; peer-reviewed; physiology; qualitative analysis; taxonomy

Paleoenvironments of the earliest stone toolmakers, Gona, Ethiopia - Quade, Jay; Levin, Naomi E; Semaw, Sileshi; Stout, Dietrich; Renne, Paul R; Rogers, Michael J; Simpson, Scott W (Geological Society of America Bulletin, 2004)
Fluvio-lacustrine sediments of the Hadar and Busidima Formations along the northern Awash River (Ethiopia) archive almost three million years (3.4 to <0.6 Ma) of human evolution, including the earliest documented record of stone toolmaking at 2.5-2.6 Ma. This paper brings together sedimentologic and isotopic evidence for the paleoenvironmental context of early hominids from both formations, but with particular emphasis on the setting for the early toolmakers. The pre-2.92 Ma record (Hadar Formation) is characterized by low-gradient fluvial, paludal, and lacustrine deposition in an undissected topography most analogous to reaches of the modern middle Awash River near Gewane. The Gona area experienced repeated deep dissection and aggradation by the Awash River, starting between 2.92 and ca. 2.7 Ma and continuing through the top of the record at <0.6 Ma (Busidima Formation). Each aggradational succession is 10-20 m in thickness and fines upward from well-rounded conglomerates at the base to capping paleosols at the top. During this period the ancestral Awash represented by these fining upward sequences was dominantly meandering and flowed northeast, as it does today. Smaller channels tributary to the axial Awash system are also extensively exposed in the Busidima Formation. Compared to the axial-system conglomerates, the tributary channels transported finer, less mature volcanic clasts mixed with abundant carbonate nodules reworked from adjacent badlands. Stone artifacts (Oldowan; 2.6-2.0 Ma) at the oldest archaeological sites are only associated with the axial Awash system, in the bedded silts or capping paleosols of the fining upward sequences. The implements were made from rounded cobbles from the channels, but manufacture and use of the tools was always away from the channel bars, on the nearby sandy banks and silt-dominated floodplains. Archaeological sites higher in the record (Acheulian; <1.7 Ma) occur in similar axial river contexts, as well as along tributary channels further removed from artifact raw material sources. Mature paleosols in the Hadar and Busidima Formations are mostly pale to darkbrown Vertisols typified by abundant clay slickensides, pseudo-anticlinal and vertical fracturing, and carbonate nodules. Such calcic Vertisols are common in the region today, demonstrating that the paleoclimate over the past 3.4 m.y. has been semi-arid and strongly seasonal. Carbon isotopic results from pedogenic carbonates in the Vertisols allow reconstruction of the proportion of C3 plants (trees and shrubs) to C4 plants (grasses) through time. The δ 13C results from the Hadar Formation prior to 2.9 Ma range from -9.3‰ to -4.1‰, indicating a dominantly forested environment but with locally substantial (average 34%) grasses on the Awash floodplain. The δ13C values from soil carbonate in the lower Busidima Formation (2.7-1.6 Ma) increase (-6.5‰ to -2.7‰) in floodplain paleosols, indicating ∼ 50% average grass cover. Vertisols of the upper Busidima Formation (< 1.6 Ma) formed on gently sloping alluvial fans adjacent to the Awash floodplain and display even more positive δ13C values, up to -1.8‰, showing that grassland dominated the margins of the active Awash floodplain. © 2004 Geological Society of America.
Keywords: Africa; Awash; Axial flow; Carbon isotopes; Cenozoic; Deposition; Early hominids; East Africa; Eastern Hemisphere; Ethiopia; First stone tools; Gona; Human evolution; Oldowan; Paleoenvironment; Paleoenvironments; Rivers; Sediments; Sub-Saharan Africa; Tools; World; dept.ant; fluviolacustrine deposit; hominid; human activity; lithic fragment; paleoenvironment; tool use

Estimating sexual size dimorphism in fossil species from posterior probability densities - Sasaki, Tomohiko; Semaw, Sileshi; Rogers, Michael J.; Simpson, Scott W.; Beyene, Yonas; Asfaw, Berhane; White, Tim D.; Suwa (Proceedings of the National Academy of Sciences of the United States of America, 2021)
Accurate characterization of sexual dimorphism is crucial in evolutionary biology because of its significance in understanding present and past adaptations involving reproductive and resource use strategies of species. However, inferring dimorphism in fossil assemblages is difficult, particularly with relatively low dimorphism. Commonly used methods of estimating dimorphism levels in fossils include the mean method, the binomial dimorphism index, and the coefficient of variation method. These methods have been reported to overestimate low levels of dimorphism, which is problematic when investigating issues such as canine size dimorphism in primates and its relation to reproductive strategies. Here, we introduce the posterior density peak (pdPeak) method that utilizes the Bayesian inference to provide posterior probability densities of dimorphism levels and within-sex variance. The highest posterior density point is termed the pdPeak. We investigated performance of the pdPeak method and made comparisons with the above-mentioned conventional methods via 1) computergenerated samples simulating a range of conditions and 2) application to canine crown-diameter datasets of extant known-sex anthropoids. Results showed that the pdPeak method is capable of unbiased estimates in a broader range of dimorphism levels than the other methods and uniquely provides reliable interval estimates. Although attention is required to its underestimation tendency when some of the distributional assumptions are violated, we demonstrate that the pdPeak method enables a more accurate dimorphism estimate at lower dimorphism levels than previously possible, which is important to illuminating human evolution. © 2021 National Academy of Sciences. All rights reserved.
Keywords: Animals; Bayes Theorem; Bayes theorem; Cuspid; Female; Fossils; Male; Models; Sex Characteristics; Statistical; animal; article; attention; canine tooth; controlled study; dept.ant; female; fossil; human; human experiment; intermethod comparison; male; nonhuman; peer-reviewed; primate; probability; sex difference; sexual characteristics; statistical model

Hominin exploitation of animal resources at the Gona Plio-Pleistocene archeological sites (Afar, Ethiopia) - Cáceres, Isabel; Rogers, Michael J.; Semaw, Sileshi; Leiss, Amanda C. (CENIEH, Centro Nacional de Investigación sobre la Evolución Humana, 2017)
Keywords: dept.ant; ⛔ No DOI found

Gona - Semaw, Sileshi; Rogers, Michael J. (The International Encyclopedia of Biological Anthropology, 2018)
Keywords: dept.ant

Late Miocene hominin teeth from the Gona Paleoanthropological Research Project area, Afar, Ethiopia. - Simpson, Scott W; Kleinsasser, Lynnette; Quade, Jay; Levin, Naomi E; McIntosh, William C; Dunbar, Nelia; Semaw, Sileshi; Rogers, Michael J (Journal of Human Evolution, 2015)
Since 2000, significant collections of Latest Miocene hominin fossils have been recovered from Chad, Kenya, and Ethiopia. These fossils have provided a better understanding of earliest hominin biology and context. Here, we describe five hominin teeth from two periods (ca. 5.4 Million-years-ago and ca. 6.3 Ma) that were recovered from the Adu-Asa Formation in the Gona Paleoanthropological Research Project area in the Afar, Ethiopia that we assign to either Hominina, gen. et sp. indet. or Ardipithecus kadabba. These specimens are compared with extant African ape and other Latest Miocene and Early Pliocene hominin teeth. The derived morphology of the large, non-sectorial maxillary canine and mandibular third premolar links them with later hominins and they are phenetically distinguishable and thus phyletically distinct from extant apes. Copyright © 2014 Elsevier Ltd. All rights reserved.
Keywords: *Fossils/ah [Anatomy & Histology]; *Hominidae/ah [Anatomy & Histology]; *Tooth/ah [Anatomy & Histology]; Afar; Animals; Ardipithecus; Ardipithecus kadabba; Ardipithecus ramidus; Biological Evolution; Ethiopia; Fossils; Hominidae; Hominina; Late miocene; Miocene; Orrorin; Tooth; Western ethiopian escarpment; anatomy and histology; animal; anthropology; canid; dept.ant; evolution; fossil; hominid; morphology; peer-reviewed; tooth

Early Pliocene hominids from Gona, Ethiopia. - Semaw, Sileshi; Simpson, Scott; Quade, Jay; Renne, Paul; Butler, Robert; McIntosh, William; Levin, Naomi; Dominguez-Rodrigo, Manuel; Rogers, Michael (Nature, 2005)
Comparative biomolecular studies suggest that the last common ancestor of humans and chimpanzees, our closest living relatives, lived during the Late Miocene-Early Pliocene 1,2. Fossil evidence of Late Miocene-Early Pliocene hominid evolution is rare and limited to a few sites in Ethiopia 3-5, Kenya 6 and Chad 7. Here we report new Early Pliocene hominid discoveries and their palaeoenvironmental context from the fossiliferous deposits of As Duma, Gona Western Margin (GWM), Afar, Ethiopia. The hominid dental anatomy (occlusal enamel thickness, absolute and relative size of the first and second lower molar crowns, and premolar crown and radicular anatomy) indicates attribution to Ardipithecus ramidus. The combined radioisotopic and palaeomagnetic data suggest an age of between 4.51 and 4.32 million years for the hominid finds at As Duma. Diverse sources of data (sedimentology, faunal composition, ecomorphological variables and stable carbon isotopic evidence from the palaeosols and fossil tooth enamel) indicate that the Early Pliocene As Duma sediments sample a moderate rainfall woodland and woodland/grassland., (C) 2005 Nature Publishing Group
Keywords: Africa; Animals; Ardipithecus ramidus; Biodiversity; Carbon; Chad; Dental Enamel; East Africa; Eastern Hemisphere; Endomorphological variables; Environment; Ethiopia; Faunal composition; Fossils; Geographical regions; Gona; Gona Wester Margin (GWM), Afar, Ethiopia; History, Ancient; Hominidae; Jaw; Kenya; Landforms; Miocene; Pan (ape); Pan troglodytes; Pliocene; Pliocene hominids; Poaceae; Radicular anatomy; Radioisotopes; Rain; Sedimentology; Sub-Saharan Africa; Time Factors; Tooth; Trees; Upper Miocene; World; Zanclea; Zanclean; article; carbon; chimpanzee; dept.ant; enamel; evolution; fauna; forest; fossil; grassland; hominid; molar tooth; paleoenvironment; premolar tooth; priority journal; rain; sedimentology

2.6-Million-year-old stone tools and associated bones from OGS-6 and OGS-7, Gona, Afar, Ethiopia - Semaw, Sileshi; Rogers, Michael J; Quade, Jay; Renne, Paul R; Butler, Robert F; Dominguezrodrigo, Manuel; Stout, Dietrich; Hart, William S; Pickering, Travis Rayne; Simpson, Scott W (Journal of Human Evolution, 2003)
Keywords: Afar; Animalia; Bone fragments; Cutmarks; Earliest stone tools; Ethiopia; Gona; Hominidae; Mammalia; Ounda Gona; Pliocene; archaeological evidence; artifact; bone; dept.ant; peer-reviewed; tool use

The first technical sequences in human evolution from East Gona, Afar region, Ethiopia - de Lumley, Henry; Barsky, Deborah; Moncel, Marie Hélène; Carbonell, Eudald; Cauche, Dominique; Celiberti, Vincenzo; Notter, Olivier; Pleurdeau, David; Hong, Mi-Young; Rogers, Michael J.; Semaw, Sileshi (Antiquity, 2018)
Gona in the Afar region of Ethiopia has yielded the earliest Oldowan stone tools in the world. Artefacts from the East Gona (EG) 10 site date back 2.6 million years. Analysis of the lithic assemblage from EG 10 reveals the earliest-known evidence for refitting and conjoining stone artefacts. This new information supplements data from other Oldowan sites in East Africa, and provides an important insight into the technological capacities and evolutionary development of hominins during this period.
Keywords: East Gona; Ethiopia; Oldowan; dept.ant; knapping; peer-reviewed; refitting

Canine sexual dimorphism in Ardipithecus ramidus was nearly human-like. - Suwa; Sasaki, Tomohiko; Semaw, Sileshi; Rogers, Michael J.; Simpson, Scott W.; Kunimatsu, Yutaka; Nakatsukasa, Masato; Kono, Reiko T.; Zhang, Yingqi; Beyene, Yonas; Asfaw, Berhane; White, Tim D. (Proceedings of the National Academy of Sciences of the United States of America, 2021)
Body and canine size dimorphism in fossils inform sociobehavioral hypotheses on human evolution and have been of interest since Darwin’s famous reflections on the subject. Here, we assemble a large dataset of fossil canines of the human clade, including all available Ardipithecus ramidus fossils recovered from the Middle Awash and Gona research areas in Ethiopia, and systematically examine canine dimorphism through evolutionary time. In particular, we apply a Bayesian probabilistic method that reduces bias when estimating weak and moderate levels of dimorphism. Our results show that Ar. ramidus canine dimorphism was significantly weaker than in the bonobo, the least dimorphic and behaviorally least aggressive among extant great apes. Average male-to-female size ratios of the canine in Ar. ramidus are estimated as 1.06 and 1.13 in the upper and lower canines, respectively, within modern human population ranges of variation. The slightly greater magnitude of canine size dimorphism in the lower than in the upper canines of Ar. ramidus appears to be shared with early Australopithecus, suggesting that male canine reduction was initially more advanced in the behaviorally important upper canine. The available fossil evidence suggests a drastic size reduction of the male canine prior to Ar. ramidus and the earliest known members of the human clade, with little change in canine dimorphism levels thereafter. This evolutionary pattern indicates a profound behavioral shift associated with comparatively weak levels of male aggression early in human evolution, a pattern that was subsequently shared by Australopithecus and Homo. © 2021 National Academy of Sciences. All rights reserved.
Keywords: Animals; Australopithecus; Bayes Theorem; Bayes theorem; Biological Evolution; Cuspid; Ethiopia; Female; Fossils; Hominidae; Humans; Male; Models; Pan paniscus; Phylogeny; Sex Characteristics; Theoretical; adult; aggression; anatomy and histology; animal; article; canine tooth; cladistics; classification; dept.ant; evolution; female; fossil; hominid; human; male; mandibular canine; maxillary canine; nonhuman; peer-reviewed; phylogeny; sex difference; sexual characteristics; theoretical model

Co-occurrence of Acheulian and Oldowan artifacts with Homo erectus cranial fossils from Gona, Afar, Ethiopia. - Semaw, Sileshi; Rogers, Michael J; Simpson, Scott W; Levin, Naomi E; Quade, Jay; Dunbar, Nelia; McIntosh, William C; Caceres, Isabel; Stinchcomb, Gary E; Holloway, Ralph L; Brown, Francis H; Butler, Robert F; et al. (Science advances, 2020)
Although stone tools generally co-occur with early members of the genus Homo, they are rarely found in direct association with hominins. We report that both Acheulian and Oldowan artifacts and Homo erectus crania were found in close association at 1.26 million years (Ma) ago at Busidima North (BSN12), and ca. 1.6 to 1.5 Ma ago at Dana Aoule North (DAN5) archaeological sites at Gona, Afar, Ethiopia. The BSN12 partial cranium is robust and large, while the DAN5 cranium is smaller and more gracile, suggesting that H. erectus was probably a sexually dimorphic species. The evidence from Gona shows behavioral diversity and flexibility with a lengthy and concurrent use of both stone technologies by H. erectus, confounding a simple "single species/single technology" view of early Homo. Copyright © 2020 The Authors, some rights reserved; exclusive licensee American Association for the Advancement of Science. No claim to original U.S. Government Works. Distributed under a Creative Commons Attribution NonCommercial License 4.0 (CC BY-NC).
Keywords: *Biological Evolution; *Fossils; *Hominidae; *Skull/ah [Anatomy & Histology]; Animals; Archaeological site; Behavioral diversity; Biodiversity; Biological Evolution; Co-occurrence; Ethiopia; Fossils; Hominidae; Hominidae/ah [Anatomy & Histology]; Hominidae/cl [Classification]; Hominins; Homo erectus; Humans; Paleontology; Single species; Skull; anatomy and histology; animal; classification; dept.ant; evolution; fossil; hominid; human; paleontology; peer-reviewed; skull

Fluvial response to Quaternary hydroclimate in eastern Africa: Evidence from Gona, Afar, Ethiopia - Stinchcomb, Gary E.; Quade, Jay; Levin, Naomi E.; Iverson, Nels; Dunbar, Nelia; McIntosh, William; Arnold, Lee J.; Demuro, Martina; Duval, Mathieu; Grün, Rainer; Zhao, Jian-xin; White, Marie; et al. (Quaternary Science Reviews, 2023)
The Busidima Formation in the Afar region, Ethiopia, spans the Quaternary and records the cultural evolution of the genus Homo. Yet, the Middle Pleistocene to Holocene fluvial environments in which early humans lived are undersampled in eastern Africa. This paper examines the stratigraphy, geochronology and paleoenvironments of the newly designated Odele Member of the uppermost Busidima Formation (<152 thousand years ago (ka)), which has received little attention despite representing a critical period in the evolution of early Homo sapiens and its migration out of Africa. The Odele Member is 40–50 m thick and is dated using tephrochronology, radiometric, luminescence, and electron spin resonance techniques. The member spans 151 to 7 ka, defined at the base by the widespread Waidedo Vitric Tuff (WAVT, 151 ± 16 ka modeled age and 95.4% credible interval - C.I.). There are two prominent erosional unconformities in the Odele Member, a lower one after the WAVT deposition with a modeled 95.4% C.I. range of 124–97 ka; and an upper one involving widespread alluvial fan incision commencing between 21.7 and 12.9 ka. The uppermost Odele Member also contains black, organic-rich mats, redox features, reed casts, and freshwater gastropods marking wetter conditions during the terminal Pleistocene and Early Holocene. A black, fine-grained relict soil coeval with the Halalalee paleosol bounds the top of the Odele Member and has mollic and vertic properties, weathering since ∼12 ka. These incision events and prominent paleosol development near/at the top of the Busidima Formation document Middle to Late Pleistocene Awash River incision to its present-day course. Paleo-rainfall estimates suggest that the Early Holocene-age Halalalee paleosol weathered under a climate with mean annual rainfall 10–15% higher than today. A compilation of radiocarbon ages from aquatic gastropods, carbonized wood and charcoal from the upper Odele Member shows wetter and possibly more vegetated conditions during late marine isotope stage (MIS) 3 and the African Humid Period (AHP) that are tightly coupled with precession-driven summer insolation maxima. These key findings suggest that periods of incision, aggregation, and landscape stability in the Odele Member have an orbital precession pacing. The Odele Member revises upward the age of the Busidima Formation to 7 ka, showing that it spans into the Holocene and now includes Middle and Later Stone Age archaeological traditions.
Keywords: Electron spin resonance; Ethiopian rift; Fluvial aggradation; Fluvial incision; Paleosol; Radiocarbon; Tephrochronology; U-series; dept.ant; pIR-IRSL; peer-reviewed